A comparative study to determine the sport branches that the classroom pre-service teachers want to be engaged in the most in their leisure time - Osman Dalaman (Selcuk University, 2014)
The purpose of the present study is to determine the sports that the university students want to do the most in their leisure which is becoming increasingly important for university students. In this regard, the present study aims to elicit the opinions of the pre-service classroom teachers from elementary education programs about the sports they want to be engaged in the most in their leisure and provide some insights into recreational facilities that should be established in campuses. The sampling of the study consists of 1082 pre-service classroom teachers from the education faculties of Necmettin Erbakan University, Mehmet Akif Ersoy University, and Muğla University in 2011-2012 academic year. The participants were selected through random sample selection method. A Likert-type questionnaire developed in line with expert opinions was used to collect data. The questionnaire consists of two parts. First part is personal information form and the second part is a scale aiming to determine the sports that the participants want to perform the most in their leisure. The Cronbach Alpha reliability coefficient of the scale to determine the sports the participants want to perform the most in their leisure was found to be .628. The collected data were analyzed through SPSS 16.0 (Statistical Package for Social Science) and for the analyses, frequencies, t-test and Chi-square were used.  The results obtained were presented in tables and interpreted. Out of the participants of the study, 336 are males and 746 are females. A gender-based significant difference was found among the sports the participants want to perform the most (p=.000, p lt;.05). The male students' attitudes towards sports (mean= 5.631) were found to be more positive than those of the female students. The sports that the students want to do the most are sequenced as follows: most preferred sport by the male students is football (87.5%), then volleyball (63.7%), swimming (60.1%), trekking (50.9%) and basketball (50.5%) and the most preferred sport by female students is volleyball (68.1%), then trekking (54.6%), swimming (53.2%) and folkdances (49.5%).